2013
DOI: 10.18060/3874
|View full text |Cite
|
Sign up to set email alerts
|

Culturally-Attuned Mentoring for Graduating Latina/o Social Workers to Foster Career Advancement

Abstract: The underrepresentation of Latinas/os in the social work profession, especially in higher levels of administration, has been amply documented. Successful Latina/o professionals can address the need for Latina/o leadership in the field by mentoring new graduates and supporting their development and career planning as they enter the professional world. This article presents an innovative mentoring program for Latina/o social work professionals conceptualized and led by the Latina/o Network of the Latina/o Networ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
4
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 21 publications
2
4
0
Order By: Relevance
“…Some of the participants revealed that their parents encouraged and supported their dream of achieving a higher level of education, which is consistent with the report of Smith and Hausafus (1998) about a mother’s attitude toward a career in science and mathematics. The findings also align with the literature that indicates parental support and encouragement are critical in fostering career advancement among Latino students and other professionals (Brown, 2002; Kosoko-Lasaki et al, 2006; Rojas-Schwan et al, 2013).…”
Section: Discussionsupporting
confidence: 87%
See 3 more Smart Citations
“…Some of the participants revealed that their parents encouraged and supported their dream of achieving a higher level of education, which is consistent with the report of Smith and Hausafus (1998) about a mother’s attitude toward a career in science and mathematics. The findings also align with the literature that indicates parental support and encouragement are critical in fostering career advancement among Latino students and other professionals (Brown, 2002; Kosoko-Lasaki et al, 2006; Rojas-Schwan et al, 2013).…”
Section: Discussionsupporting
confidence: 87%
“…Familismo is a “cultural value that stresses attachments, reciprocity, and loyalty to family members beyond the boundaries of the nuclear family” (Andres-Hyman, Ortiz, Añez, Paris, & Davison, 2006, p. 696). This family support factor is reported in several Latino studies (Kosoko-Lasaki, Sonnino, & Voytko, 2006; Rojas-Schwan, Negroni, & Santiago-Kozmon, 2013). Kosoko-Lasaki, Sonnino, and Voytko (2006) reported that having a support system and familial support was beneficial to the success and empowerment of Hispanic college students.…”
Section: Related Literaturesupporting
confidence: 70%
See 2 more Smart Citations
“…Indeed, mentoring has been shown to ease cultural identity transitions within other fields. [53][54][55] Mentors may act as social bonds who help refugee doctors to both acquire knowledge and conduct identity work.…”
Section: Discussionmentioning
confidence: 99%